2004
DOI: 10.1042/bj20031187
|View full text |Cite
|
Sign up to set email alerts
|

Role of transient receptor potential canonical 6 (TRPC6) in non-transferrin-bound iron uptake in neuronal phenotype PC12 cells

Abstract: Cells take up transferrin-bound iron or NTBI (non-transferrin-bound iron). After treatment with NGF (nerve growth factor), PC12 cells exhibited a neuronal phenotype and an increase in the NTBI uptake (55Fe2+ or 55Fe3+). We loaded the cells with the dye calcein, whose fluorescence increases in the presence of Ca2+ but is quenched with Fe2+ or Fe3+. When examined using calcein fluorescence or radioactive iron, DAG (diacylglycerol)-stimulated NTBI entry was more in NGF-treated PC12 cells compared with untreated c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(34 citation statements)
references
References 44 publications
1
33
0
Order By: Relevance
“…To confirm the effects of intracellular hydroxyl radical, cells in the study of Ishii et al [53] were pretreated with FeSO 4 for 1 h, and then H 2 O 2 was added after washing out extracellular Fe 2+ in TRPM2-expressing HEK293 cells and beta-cell line RIN-5F cells. Many investigators reported that various types of cells, including HEK293, take up Fe 2+ within a few minutes [55,56]. By pretreatment with FeSO 4 for 1 h, addition of H 2 O 2 significantly activated TRPM2, suggesting that the intracellularproduced hydroxyl radical is responsible for activation of TRPM2 [53].…”
Section: Gating Trpm2 Cation Channel By Adprmentioning
confidence: 99%
“…To confirm the effects of intracellular hydroxyl radical, cells in the study of Ishii et al [53] were pretreated with FeSO 4 for 1 h, and then H 2 O 2 was added after washing out extracellular Fe 2+ in TRPM2-expressing HEK293 cells and beta-cell line RIN-5F cells. Many investigators reported that various types of cells, including HEK293, take up Fe 2+ within a few minutes [55,56]. By pretreatment with FeSO 4 for 1 h, addition of H 2 O 2 significantly activated TRPM2, suggesting that the intracellularproduced hydroxyl radical is responsible for activation of TRPM2 [53].…”
Section: Gating Trpm2 Cation Channel By Adprmentioning
confidence: 99%
“…In particular, Mwanjewe and Grover [31] investigated the role of the members of the canonical subfamily of TRP (TRPC [32]) that are considered possible candidates for store-and receptor-operated calcium channels. These nonselective cationic channels might therefore account for the calcium influx that is observed after store depletion or phospholipase C activation by G-protein-coupled receptors [30].…”
Section: Ntbi Uptake By Pathways Common To Calcium Influxmentioning
confidence: 99%
“…leukocyte chemotaxis or lymphocyte-target cell conjugation), and has minimal effects on cell function (De Clerck et al, 1994). Therefore, the calcein-release assay and fluorescence microfluorometry (Mwanjewe and Grover, 2004) were used to verify cytotoxicity and screen for qualitative changes in ionic metabolism. In brief, C17.2 cells were cultured in 35-mm petri dishes for 24 h, the center bottom having been removed and replaced with glass coverslips.…”
Section: Microfluorometrymentioning
confidence: 99%